Seawater salinity modelling based on electromagnetic wave characterization - Imadeldin Elsayed Elmutasim; Izzeldin Ibrahim Mohamed; Khalid Hamid Bilal (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Wireless communications have experienced tremendous growth, and improving their performance based on specific parameters requires an accurate model. Salt seawater, being an abundant resource, could play a crucial role in various applications such as enhancing electrical conductivity, monitoring security, improving battery power efficiency, and creating liquid antennas. Salinity is an essential factor to consider when developing these applications. This paper focused on investigating the electromagnetic properties of seawater salinity in the context of marine wireless communications. The results of the study showed that salinity has a significant impact on the Fresnel reflection coefficient in terms of magnitude, phase shift, and polarization, and can either constructively or destructively affect it. The new model paved the way for the development of an integrated salt seawater model that addressed the complex salinity issues involved in these applications.